Euler-Euler CFD simulation of the fuel reactor of a 1 MWth chemical-looping pilot plant: Influence of the drag models and specularity coefficient. (15th July 2017) - Sharma, Raman; May, Jan; Alobaid, Falah; Ohlemüller, Peter; Ströhle, Jochen; Epple, Bernd
Highlights: Euler-Euler CFD simulation of fuel reactor of the coal fired CLC pilot was performed. Different drag models and specularity coefficients were investigated. Pressure drops at different heights of the fuel reactor were reproduced accurately. Simulated outlet gases were compared with experimental data, showing good agreement. More outgoing mass flow of ilmenite for higher specularity coefficient. Abstract: Euler-Euler (two-fluid) model was applied to simulate the hydrodynamics of the fuel reactor of the 1 MWth chemical-looping system with Geldart B particles. The drag models of Wen-Yu and Gidaspow were used along with the restitution coefficient of 0.6 and the specularity coefficient of 0 and 1. The results of the numerical simulation were compared with the experimental data from the 1 MWth chemical-looping combustion pilot plant at Technische Universitӓt Darmstadt. The volume fraction of methane agrees well with the measurements for all cases, while the predicted volume fractions of CO2, CO and H2 were different from the experimental values due to improper reaction of CO and H2 with ilmenite. Predicted pressure drop values along the height of the fuel reactor were similar to the experimental values for all cases. Nevertheless all cases overestimate the pressure at the bottom of the reactor by about 10 mbar. Keeping the drag model constant, the outgoing mass flow of the ilmenite was higher for the specularity coefficient (ϕ = 1) as compared to the specularity coefficient of (ϕ = 0). This is due to higher rate of reaction for (ϕ = 1), which is increasing the temperature of the outgoing gases and therefore increasing the gas velocity, resulting in a higher entrainment of ilmenite particles..